2022
DOI: 10.1071/hc22094
|View full text |Cite
|
Sign up to set email alerts
|

Interventions designed to improve uptake of allopurinol for gout treatment in Aotearoa New Zealand: a scoping review

Abstract: Introduction.Gout in Aotearoa New Zealand (NZ) remains an equity issue. The prevalence in Pacific and Māori people is one of the highest internationally. Although Pacific and Māori experience earlier onset and higher burden of gout, which can severely impact their quality of life, their management of it is often sub-optimal. Aim. To conduct a scoping review of the NZ literature for interventions to improve the uptake/management of allopurinol for gout and their evaluation. Methods. Databases Medline, Scopus, E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…These findings are in line with previous studies, emphasizing the importance of patient education on the chronic nature of gout and the importance of consistent adherence to prevent future attacks and long-term complications [ 20 ]. By fostering a comprehensive understanding of gout as a chronic condition and elucidating the benefits of sustained medication use, websites can foster informed decision-making among patients and promote a long-term commitment to therapy [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…These findings are in line with previous studies, emphasizing the importance of patient education on the chronic nature of gout and the importance of consistent adherence to prevent future attacks and long-term complications [ 20 ]. By fostering a comprehensive understanding of gout as a chronic condition and elucidating the benefits of sustained medication use, websites can foster informed decision-making among patients and promote a long-term commitment to therapy [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…In Aotearoa/New Zealand, other community-based gout management strategies have been described, including pharmacist-led care, practice management approaches and multidisciplinary interventions involving kaiawhina (M aori community health workers), general practitioners, pharmacists, nurses, rheumatologists and other clinic staff. 26 Despite proequity intent, some of these interventions, including community pharmacist care, resulted in increased inequity, with non-M aori, non-Pacific peoples more likely to achieve clinical success. 27 Many barriers to effective long-term gout management exist in clinical practice, particularly related to social determinants of health, structural and funding demands and competing demands with other long-term health problems.…”
Section: Cardiometabolic Risk Assessment and Managementmentioning
confidence: 99%
“…It is uncertain whether this study of mostly older English men can be directly translated into other healthcare settings, particularly for younger people who may not be able to get to practices during ‘clinic hours’. In Aotearoa/New Zealand, other community‐based gout management strategies have been described, including pharmacist‐led care, practice management approaches and multidisciplinary interventions involving kaiawhina (Māori community health workers), general practitioners, pharmacists, nurses, rheumatologists and other clinic staff 26 . Despite proequity intent, some of these interventions, including community pharmacist care, resulted in increased inequity, with non‐Māori, non‐Pacific peoples more likely to achieve clinical success 27 .…”
Section: Improving Outcomes For People With Goutmentioning
confidence: 99%
“…Previous studies have shown that chronic conditions are associated with health literacy, and improving health literacy may be a prospective method to help patients better manage their health [ 17 ]. The literature shows that the main reason for the discontinuation of urate-lowering drugs among gout patients is poor health literacy [ 18 ] and suggests that health professionals utilize online booklets to increase the health literacy of these patients for controlling SUA levels [ 19 ]. However, health literacy has not been examined in AHU patients.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have demonstrated that greater social support is associated with better self-rated health and fewer health-impairing, such as having lower SUA levels [ 21 , 22 ]. [ 19 ]Previous studies have shown that social support has a positive relationship with health literacy and has chain-mediating effects on education level, medication adherence [ 23 ], and self-management [ 24 ]. For gout patients, studies have shown that self-management behaviour is related to social support [ 25 ].…”
Section: Introductionmentioning
confidence: 99%